Gambaran Proses Pembuatan Transfemoral Prosthesis Menggunakan Polycentric Knee Joint Untuk Pasien Amputasi Atas Lutut - Ismi Dwi Syafitri; Nur Rachmat (Poltekkes Kemenkes Surakarta, 2018)
Abstract : Transfemoral Amputasi, Transfemoral Prosthesis, Polycentric Knee Joint. World Health Organization (WHO) estimated that there are 40 million amputees throughout the developing countries. Amputation in the lower limbs reached 85% -90% of all amputations. Transfemoral amputation because of this amputation occurs in the thigh that passed through the femur bone. Amputation causes significant gait abnormalities. amputation levels increased, the functional level is reduced, and the characteristic of the gait abnormality is immediately apparent. Transfemoral Prosthesis is artificial limb that made for above knee amputation. making process of transfemoral prosthesis includes assessment, measurement, casting, fabrication, fitting, finishing. Of all components for transfemoral patients, prosthetic knee joints are the most important components that can affect to gait stability. The choice for the type of popular passive knee mechanism is polycentric knee. The polycentric knee joint mechanism, linkage of 4 and 6 bar mechanisms have been used to increase stability during the stance and kinematic phase of the swing phase.